Boosting Government Assets as A Revenue Center: Risk and Treatment - Dwi Martani; Nurul Ainuzzahrah (Profesional Muda Cendekia Publishing, 2023)
The Ministry of Finance, through the Directorate General of State Assets Management (DGSAM), strives to increase the contribution of asset management as a source of Non-Tax State Revenue through the Asset Utilization mechanism (in the form of assets rent, etc.). However, empirical data indicates that Asset Utilization activities are not optimal. This study aims to conduct a risk assessment of the government assets rental business process. The study was conducted qualitatively following the risk assessment steps according to ISO 31000:2018 Risk Management. Based on data obtained (by document analysis and interviews) and referring to the organization's risk appetite, the risk assessment shows that eight significant risks need to be anticipated and mitigated by DGSAM related to the assets rental business process. To increase the effectiveness of the assets rental business process in generating Non-Tax State Revenue, we recommend DGSAM as Assets Manager to increase the effectiveness of control in the assets rental business process and implement risk mitigation as an embedded strategy in improving asset management.